The Traditional and Innovative Technologies of Vocational Guidance Work with Pupils and Students - Sibgatova, Kadriya I.; Ilchinskaya, Elena P.; Bastrikova, Elena M.; Kuramshina, Lyudmila L.; Makarov, Alexandr L.; Chernova, Natalya Y.; Khairullina, Elmira R.; Murugova, Vera V. (International Review of Management and Marketing, 2016)
Today, considering the needs of the Russian economy, the content and technology of training in career counseling from the point of view of practice is not sufficiently developed. Thus, a search for new forms, methods and means of conducting career guidance with students is necessary. This article offers a broad range of technologies and their optimal combination in career guidance work with pupils in the integrated system "school – University – enterprise". A leading approach to the study of this problem is an integrative approach that leads to the necessity to use both traditional and innovative technologies which contribute not only to effective assimilation of knowledge, but also early social adaptation of the prospective students to University conditions. Presented in the study traditional and innovative technologies of career guidance work with students (project method, role play, portfolio, Internet technologies, comprehensive and career-oriented excursions), as well as the possibility of using information and educational potential of professional education institutions and enterprises for pupils' vocational guidance in the context of their successive socialization contribute to the formation of professional identity, consciousness in the choice of the future profession of secondary schools' students, as well as the selection of their own individual educational trajectories and to their adaptive abilities' disclosure for future professional activity. The article is valuable for teachers and faculty of educational and vocational institutions in organizing and conducting of career guidance with students, applicants and students. Keywords: Career Guidance, Innovative and Traditional Technologies, Students, University. JEL Classifications: A23, I23, I26